Production of Rubber Seed Oil: Study of Parameters and some Food Oil Properties - Yuniar, Rizka Ayu; Pusfitasari, Memik Dian; Kumalaningrum, Amalia Nur; Malcheli, Etni Jechonia; Saleha, Shela; Silmina, Silmina (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2024)
Rubber seeds are one of the plantation commodities that are underutilized by the Indonesian people, apart from being the generative seeds of rubber trees. Rubber seeds have a reasonably high vegetable oil content of 68.53% with a carbohydrate content of 6.99%, protein content of 17.41%, and ash content of 3.08%. This study aimed to obtain food oil from rubber seeds with fewer chemicals and more affordable production costs. This study investigates the properties of food oil from rubber seeds and analyzes the cyanide content. The oil extracted using the traditional method yielded an 8.48% oil content. The rubber seeds were soaked for four days with rice husk charcoal (1:1) to reduce cyanide levels, followed by cooking to obtain the oil and bleaching with bentonite for purification. The oil was characterized according to Indonesian National Standards (SNI), assessing cyanide content, organoleptic properties, water content, acid values, and peroxide numbers. The resulting oil had a density of 0.87 g/cm and a cyanide content of 0.54 ppm. The tests showed a water content of 0.04%, an acid value of 0.4 mg NaOH/g, and organoleptic properties that met SNI standards. However, the peroxide value of 13.5 meq O2/kg was slightly above the standard, making the oil non-edible.